Detecção e localização de proteínas relacionados às MRJPs e de suas possíveis proteínas sítio-ligantes no cérebro e glândula hipofaringeal da abelha Apis mellifera - Peixoto, Leonardo Gomes (2006)
ABSTRACT - CHAPTER I The major royal jelly proteins (MRJPs) are a honeybee (Apis mellifera) unique protein family, which highly expressed in the hypopharyngeal gland of the worker bee. To identify proteins related to the MRJPs in the bee s nervous system, antibodies were immunopurified and assayed to reveal polypeptides that are reactive to these antibodies in the bee brain and hypopharyngeal gland. The identities between the MRJPs sequences were analyzed through bioinformatics, and the distribution of the MRJPs in these tissues was investigated immunohistochemically. Among some hymenoptera species investigated only Apis mellifera showed polypeptides that cross-reacted to the anti-MRJP1 and anti- MRJP total antibodies. Three polypeptides, p57, p70 and p128, were detected in the honeybee head, brain and hypopharyngeal gland with some detection pattern upon differences of bee caste, age and brain areas investigated. The results showed: a) p57 was is the only polypeptide immunoprecipitated by anti-MRJP1 suggesting that it may be related to a MRJP1 brain specific protein; b) p70, based in the relative molecular mass, may be related to MRJP3 and c) p128 is a new not yet reported MRJP-like protein in the brain sections of the bee brain and hypopharyngeal gland probed with both anti-MRJP total and anti-MRJP1 showed the localization of MRJPs in different brain areas such as mushroom bodies, optical and antennal lobe and a strong staining in the whole gland. In this study, we showed polypeptides immunoreactive to the antibodies for the MRJPs in the brain and hypopharyngeal gland of A. mellifera. The localization of these MRJPs in regions of the brain may contribute to elucidate the biological role of this family of proteins present in these honeybees. ABSTRACT - CHAPTER II The major royal jelly proteins (MRJPs) of Apis mellifera honeybee are water soluble proteins with restricted homology to Yellow proteins described for Drosophila melanogaster. MRJPs transcripts found in the workers honeybees brain and the MRJPs localization in specific regions of A. mellifera brain opened perspectives for the study about MRJPs related proteins in the honeybee nervous system. The MRJP1 antigenic regions and targets proteins to MRJPs in honeybee brain were investigated using 21 peptides selected by Biopanning and generated by phage display. The pool of these peptides was used as probe to immunolocalize MRJP1-putative binding protein. The MRJP1 identified sites had showed identicals regions in all the others MRJPs analyzed. The peptides that mimetize MRJP1 antigenic regions were imunnodetected in the selected phage samples. The MRJP1 putative binding protein were imunnolocalized in the mushroom bodies, optic lobes and hypopharyngeal gland of all the A. mellifera honeybee castes. This study appoints the presence of MRJPs binding proteins in the honeybee nervous system, suggesting a new interaction of these proteins with its ligands in A. mellifera honeybee brain.